G388(P) Stamp: a long term, ongoing prescribing qi project to improve prescribing and medication safety. (12th March 2018) - Trivedi, A; Styles, K; Bate, T; Ajitsaria, R
Abstract : Aim: We describe an ongoing quality improvement project focusing on paediatric prescribing for medical, surgical and oncology patients in a district general hospital. The project is called STAMP – 'Safe Treatment and Administration of Medicine in Paediatrics'. The aim of the project was to identify why local errors were happening, improve feedback to prescribers when errors were made and to decrease the rate of these errors through multiple interventions. Method: Divisional lead pharmacist collected weekly error data for nine months. Individual feedback given to prescribers. Error data shared with the paediatric team via departmental instant text message group. Results: On average 185 prescriptions reviewed per week. Mean error rate 5.2% and worst error rate 12.6%. The most common errors were incorrect or missing frequency and incorrect dose. There was an initial see-saw error rate and a period of improved prescribing in July and August 2017 which we felt was secondary to the teaching highlighting common errors. However this improvement was not sustained. We noticed a decrease in errors when the ward was less busy which is consistent with prescribers reporting frequent interruptions and increased errors when there were new medical staff. As a result of feedback from prescribers we have made multiple interventions including sharing anonymous 'error of the week' examples on group text message service as a quiz with answer, new medication guideline for surgical and orthopaedic for their most frequently prescribed medications, departmental teaching, and prescribing station with prescribing resources to encourage prescribers to move to an interruption–free zone. Conclusion: Although we have not yet been able to demonstrate sustained improvements in prescribing error rates, we believe multiple small changes and a strong STAMP team are most likely to bring about a culture of safer prescribing within our department. We feel that our most significant steps so far are the teaching sessions and improved personal feedback to prescribers. We hope the new prescribing station will decrease interruptions during prescribing. We need to reach out to our junior surgical and orthopaedic colleagues who do not attend our teaching and may benefit from additional prescribing support.